Landasan Penyelenggaraan Pendidikan Inklusi di Sekolah Alam Tangerang - Nurfadillah, Septy; Saadah, Lailatus; Cahyani, Ajeng Putri; Haya, Aqila Fadiya; Rachma, Salsabila Nabira; Umayyah, Nida; Huzaemah, Huzaemah (MASALIQ, 2022)
Education is a basic right of every Indonesian citizen, including those with special needs. Inclusive education is an educational service system that requires children with special needs to attend neighborhood schools in regular classes with their peers. In Indonesia, especially in primary schools, it has not been accompanied by a vision of education that is not based on an inclusive ethos that prioritizes diversity and equality in educational attainment. Inclusive education is an approach that aims to change the education system by removing barriers that can prevent all students from fully participating in education. The type of research used is a qualitative research method in the form of questions and answers with a case study approach to carry out observations by interviewing. The results obtained in this study were based on the location of the natural school in Cipondoh, Tangerang city, so it was found in the interview that there were several children with special needs in the school with a population of 11 students with one teacher supervisor in each class so that ABK students got a good focus on learning. So that inclusive education is needed in every school to provide opportunities for children with special needs.